Madhyakālīna pūrvāñcalaka Vaishṇava sāhitya - Jhā, Rājeśvara (Maithilī Akādamī, 1977)
On medieval Vaishnavite literature from eastern India
In Devanagari-Schr., Maithili
Keywords: Vaishnava literature; Maithili / History and criticism; Vaishnava; Maithili; Literatur